The science of language is the beginning of all sciences - Salkynbay А B (Journal of Oriental Studies, 2016)
This paper studies the scientific positions of outstanding scientist of East Abu Nasir Al-Farabi on linguistics and speech. Analyzed conclusions of the thinker in his treatise “On the origin of science”, it argues that the basis of any science is the science of language, which begins with the expression, acquire and teaching knowledge, with questions and answers. From the point of view of modern science thought of Al-Farabi on linguistics reflects the study of the structure of speech, "the philosophy of language", "grammar", "cognitive and applied linguistics." The article focuses on the classification of sciences of al-Farabi, among which he highlights the science of language and its sections in the treatise "The Book of the Enumeration of the Sciences." Since language is an inherent part of human society, human nature, social life, the study of the Sciences depends on its language. Language and thought – are the essence of a human. In conclusion it indicates that the perfection of a human depends on his management thinking and speech. In conclusion indicates that the perfection of a human depends on its management thinking and speech.